Aerobic interval training in freestyle swimming - Wahyudi M. E.; Hendrayana, Y.; Ma`mun, A.; Mulyana, B. (International Journal of Human Movement and Sports Sciences, 2020)
This research was conducted so that the endurance and speed of swimming athletes can be increased and prepare young swimmers to be able to reach the time requirements in following the provincial championship. Problems found in the field, athletes train in the conventional way, and training programs are arranged based on the trainer's experience. This is the basis for the use of aerobic interval training for young swimmers because it can form training early by using a proven theoretical basis that can increase the time in swimming. The research began by revealing the ability of the freestyle athlete in the swimming club through aerobic interval training in order to have maximum endurance and speed. This training involved 18 athletes in the age range of 10-15 years. The success of the training is known through data obtained from the best time during aerobic training in the 50m freestyle swimming. Swimming time measurement uses a stopwatch so that freestyle swimming time is known before and after training. Time achievement that has been obtained is done different tests to see the effect of interval training on swimming time speed. The final measurement results show that the athlete's time achievement in freestyle swimming changes after being given aerobic interval training. The results of this study will support the achievement of best time young swimmers to take part in the National Sports Week by continuing training using theoretically and empirically tested training programs.